Benign tumors in gynecology and obstetrics. Benign ovarian tumors, diagnosis, clinical management and adolescence. - Guillén Araoz, Félix (2015)
We thought it appropriate that, on the basis of our experience, we can draw some guidance and conclusions that will lead to better diagnostic approaches, without repeating other experiences that are different from ours. For these reasons we will base our discussion on a statistical review of 16 years (1964-1980) on GENERAL HOSPITAL HEALTH CENTER BASE TRUJILLO, on the incidence of ovarian tumors, diagnosis and treatment, focusing on the age group of 10 to 19, comprising the adolescent group.